2018
DOI: 10.1111/bjd.17082
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive skin can be small fibre neuropathy: results from a case-control quantitative sensory testing study

Abstract: The decrease in HPT in patients with SSS compared with controls suggests the presence of hyperalgesia, probably due to the damage of C-fibres. These findings, as well as the increased DN4 and NPSI scores, strengthen the neuronal hypothesis of SSS and are new arguments for consideration of SSS as small fibre neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 37 publications
1
42
0
3
Order By: Relevance
“…26 Recently, another study suggested that SS could be a small-fibre neuropathy. 27 The diversity of triggering factors suggests that there may be an abnormal activation of sensory receptors from the transient receptor protein family because these proteins are the only proteins known to be activated by physical and chemical factors. 1 The exact role of these triggering factors needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, another study suggested that SS could be a small-fibre neuropathy. 27 The diversity of triggering factors suggests that there may be an abnormal activation of sensory receptors from the transient receptor protein family because these proteins are the only proteins known to be activated by physical and chemical factors. 1 The exact role of these triggering factors needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence for the involvement of nerve endings in SS, which should be considered as a small-fiber neuropathy (19,20). Consequently, the length of altered nerve endings is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study, 21 subjects with and 21 subjects without sensitive skin were compared with a significant decrease in the heat-pain threshold detection in the sensitive skin group compared with the control group. 46 Conversely, vibration and cold threshold detection revealed no difference. These findings are similar to those observed in smallfibre neuropathies.…”
Section: Role Of Epidermal Nerve Endingsmentioning
confidence: 94%
“…9 Without excluding other possible explanations, the role of the nervous system in the development of sensitive skin is crucial and a growing body of evidences supporting this hypothesis. 46 In a recent epidemiological study on 5000 volunteers, very sensitive skin was twice as common in people with irritable bowel syndrome, 47 considered as secondary to peripheral nervous system alterations. 46 In a recent epidemiological study on 5000 volunteers, very sensitive skin was twice as common in people with irritable bowel syndrome, 47 considered as secondary to peripheral nervous system alterations.…”
Section: Role Of Epidermal Nerve Endingsmentioning
confidence: 99%
See 1 more Smart Citation